Serum biomarker profiles of interleukin-6, tumor necrosis factor alpha, matrix-metalloproteinase-2, and vascular endothelial growth factor in endometriosis staging (Faculty of Medicine Universitas Indonesia, 2013)
Background: The focus of this study was to compare serum biomarkers: interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), matrix-metalloproteinase-2 (MMP-2) and vascular endothelial growth factor (VEGF) in endometriosis stage I-II and stage III-IV. Methods: This is a cross-sectional study. Forty endometriosis patients were diagnosed using laparoscopy procedure. Serum sample was taken before the surgery. The serum biomarkers (IL-6, TNF-α, MMP-2, and VEGF) were analyzed with ELISA method at the end of research. Mean of serum biomarkers in endometrosis stage I-II and stage III-IV were compared using unpaired t-test. Variables that show significant mean difference were tested using ROC measurement and the optimal cut-offÂ point was determined. Results: There was no significant difference in mean serum biomarkers level of IL-6, TNF-α, and MMP-2 between endometriosis stage I-II and stage III-IV (1.58 ± 0.78 vs 1.55 ± 0.98 pg/mL, 1.5 ± 0.47 vs 1.49 ± 0.29 pg/mL, and 152.04 ± 27.32 vs 140.98 ± 28.08 ng/mL, respectively). On the other hand, the comparison of VEGF level in endometriosis stage I-II and stage III-IV demonstrated significant difference (289.76 ± 188.13 vs 581.29 ± 512.85 pg/mL (p < 0.05)). Mean difference of VEGF had AUC of 74.5%. Optimal cut-off point for VEGF was 314.75 pg/mL with sensitivity 78.6% and specificity 69.2%. Conclusion: This study showed that serum biomarkers of VEGF level (but not IL-6, TNF-α, and MMP-2) can be used to measure the degree of severity in endometriosis. VEGF level of 314.75 pg/mL represents the cut-off point between lower and higher stage of severity.